Análise da presença de agentes mutagênicos nas águas do Rio Pitimbú/RN - Egito, Lucila Carmem Monte (2006)
The Pitimbu River is located at the oriental portion of the State of Rio Grande do Norte, including three importants cities named Macaíba, Parnamirim e Natal. Although its high importance as a water source, which supplys great part of the South Zone of the Natal city, this river receives a large quantity of domestic and industrial waste water without treatment. The Pitimbu River headhas its river-head located in the city of Macaiba, goes through Parnamirim, then it flowing into at the Jiqui Lake in Natal. The aim of this study was to evaluate, qualitatively and quantitatively, the environmental quality of the Pitimbu River by genotoxicity bio-assays, which are important tools for genetics toxicological evaluation. In this work, five samples sites, distributed along the river, were used to collect water samples. Another point site, located near Jiqui lake, was used to collect drinkable water, which was treated by CAERN, the water treatment entreprise of Rio Grande do Norte. The following assays where used to evaluate the quality of these samples: Allium cepa assay; Comet assay; Micronuclei (MN) assay; and Ames test. For the Allium cepa assay, sixteen specimes where used for each water sample from the sample sites. In this assay both microscopic, like cytogenetic damage, and macroscopic aspects, as morphological variation were evaluated. Red blood cells from periferical blood of the Crenicichla menezesi native specie were used not only for the MN assay, but also for the Comet assay. These fishes were collected at different points on the Pitimbu River and the negative control was developed using fishes of the same species that were bring to the laboratory and maintained for 100 days in the optimal experimental conditions. For the Ames test, TA100, YG1042, TA98 and YG1041 strains were used in the directed method without metabolic activation. The results found by the Allium cepa assay showed that two water sample sites induced increase of mitotic index (IM). Additionally, compared to the control, all the water samples increased the chromossomal aberrations frequency and/or micronucleus. Among the sample sites, two also showed an abnormal growth rate in its root and two samples induced morphological alteration. With the MN test in red blood cells, a high frequence of MN was observed in tree sample. By comparing all the results obtained on the water sample points and with the negative control, a significant variation on the MN frequency was observed. Positive results were also observed for the same sample to water test by the Comet assay. These results allow concluding that the proposed specie Crenicichla menezesi has a good profile as a bio-indicator for the evaluation of environmental water quality and the MN and comet test can be usuful for in situ evaluation. By the Ames test, it was possible to detect the mutagenic activity on the waters from the Pitimbu River in different levels of mutagenicity. This result suggests that this river has several substances that induced changes directly to the DNA. The mechanisms involved to this phenomenon could be by both processes, by changing of the reading frame and by nucleotide substitution. These data set indicate the presence of mutagenic agents, which can represent in risk to biot and human beens